China and the world: South-south cooperation for inclusive, green growth - Kishan Khoday; Leisa Perch (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Sustainable development in a multi-polar world] World leaders convened for the UN Conference on Sustainable Development (Rio+20) in June 2012, marking 20 years since the 1992 Rio Earth Summit, and at a time of rapidly increasing pressures on the planet's ecosystems and impacts on the poor and vulnerable members of society. Rio+20 focused on two closely related solutions to the world's challenges - new institutional frameworks for sustainable development, and the drive to a green economy defined as an economy 'that results in improved human well-being and social equity, while significantly reducing environmental risks and ecological scarcities' (UNEP, 2012). (...)
Keywords: 330; Nachhaltige Entwicklung; Süd-Süd-Beziehungen; China